Down-regulation of Fusarium oxysporum endogenous genes by Host-Delivered RNA interference enhances disease resistance - Hu, Zongli; Parekh, Urvi; Maruta, Natsumi; Trusov, Yuri; Botella, Jose R. (Frontiers in Chemistry, 2015)
Fusarium oxysporum is a devastating pathogen causing extensive yield losses in a variety of crops and development of sustainable, environmentally friendly methods to improve crop resistance is crucial. We have used Host-Derived RNA interference (HD-RNAi) technology to partially silence three different genes (FOW2, FRP1 and OPR) in the hemi-biotrophic fungus Fusarium oxysporum f. sp. conglutinans. Expression of double stranded RNA molecules targeting fungal pathogen genes was achieved in a number of transgenic Arabidopsis lines. F. oxysporum infecting the transgenic lines displayed substantially reduced mRNA levels on all three targeted genes, with an average of 75%, 83% and 72% reduction for FOW2, FRP1 and OPR respectively. The silencing of pathogen genes had a clear positive effect on the ability of the transgenic lines to fight infection. All transgenic lines displayed enhanced resistance to F. oxysporum with delayed disease symptom development, especially FRP1 and OPR lines. Survival rates after fungal infection were higher in the transgenic lines compared to control wild type plants which consistently showed survival rates of 10%, with FOW2 lines showing 25% survival; FRP1 lines 30-50% survival and FOW2 between 45-70% survival. The down-regulation effect was specific for the targeted genes without unintended effects in related genes. In addition to producing resistant crops, HD-RNAi can provide a useful tool to rapidly screen candidate fungal pathogenicity genes without the need to produce fungal knockout mutants.